Microbiological evaluation of milk samples positive to California Mastitis Test in dairy buffalo cows (Buballus bubalis) - Bonini Pardo, R. [UNESP]; Mendoza-Sánchez, G. [UNESP]; Nader Filho, A. [UNESP]; Santos, Taís A.B [UNESP]; Langoni, H. [UNESP]; Tonhati, H. [UNESP]; Ferreira, E. B.S.; Ravena, D. L.; Oliveira, M. E.A.; Sturion, D. J. (My University, 2007)
In order to observe the microbiological status of CMT positive samples, 734 apparently health mammary quarters from buffalo cows were submitted to physical evaluation, strip cup test and CMT. After milk samples inoculation in 10% ovine blood agar base media and in MacConkey agar and incubation under aerobic condition for 72 hours at 37°C, identification was proceeded. According to CMT, 227 quarters (30,93%) were positive, among them 73 (32,16%) presented 1+ reaction, 53 (23,35%) were 2+ and 101 (44,49%) were 3+. Microbiological exams of such samples were positive in 147 (64,76%) out of 227 CMT positive samples and among the remaining 72 (31,72%) were negative and 8 (3,52) were contaminated. In the 147 microbiological positive samples 204 bacteria were found in pure or associated growth and the most frequent agents were: Corynebacterium sp (59,25%); Staphylococcus sp (17,65%) among which 86,11% were coagulase negative and 13,89% were coagulase positive; and Micrococcus sp (6,37%). The results revealed that, excluding the eight contaminated samples, 147 (67,12%) quarters out of 219 CMT positive could be considered as bacteria-carrier and that even in a smaller percentage false-positive results can cause problems in a sanitary program for mastitis control in dairy buffalo cows.
Keywords: CMT; Dairy buffalo cows; Microorganisms; Subclinical mastitis